2014
DOI: 10.1007/s11739-014-1157-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of metformin on vitamin B12 deficiency: a meta-analysis review

Abstract: Metformin is the only biguanide oral hypoglycemic drug, that is used to treat patients with type-2 diabetes mellitus. There are some reports of metformin being associated with decreased serum levels of vitamin B12 (VB12). The objective of this study is to systematically analyze the impact of metformin on the frequency of VB12 deficiency and serum levels of VB12. A search of various databases provided 18 retrospective cohort studies and 11 randomized controlled trials. Pooled estimates of odds ratio with 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 33 publications
(33 reference statements)
6
69
0
6
Order By: Relevance
“…Most intervention trials in this review were only of short duration (up to 4-months) but indicated a statistically significant reduction in B12 levels beyond the 6-weeks period and in some cases led to frank deficiency. Our fixed effects meta-analysis of four intervention trials showed a statistically significant lowering of vitamin B12 levels by 57 pmol/L(95% CI: -35 to -79).This reduction in B12 levels could be clinically significant in causing frank deficiency In terms of previous research, our results supports the recent meta-analysis by Niafar et al(2015) which found a reduction of 66 pmol/L (-65.8 (95% CI -78.1 to -53.6 pmol/L p<0.00001) for metformin use in an analysis of a more heterogeneous group of patients (including studies of specific groups of patients with hyperlipidaemia and polycystic ovarian syndrome) [8]. Our result is also similar to that of Liu et al (2014) [9], who found a reduction of 54 pmol/L in a meta-analysis, but included rosiglitazone as a control in the pooled estimate.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Most intervention trials in this review were only of short duration (up to 4-months) but indicated a statistically significant reduction in B12 levels beyond the 6-weeks period and in some cases led to frank deficiency. Our fixed effects meta-analysis of four intervention trials showed a statistically significant lowering of vitamin B12 levels by 57 pmol/L(95% CI: -35 to -79).This reduction in B12 levels could be clinically significant in causing frank deficiency In terms of previous research, our results supports the recent meta-analysis by Niafar et al(2015) which found a reduction of 66 pmol/L (-65.8 (95% CI -78.1 to -53.6 pmol/L p<0.00001) for metformin use in an analysis of a more heterogeneous group of patients (including studies of specific groups of patients with hyperlipidaemia and polycystic ovarian syndrome) [8]. Our result is also similar to that of Liu et al (2014) [9], who found a reduction of 54 pmol/L in a meta-analysis, but included rosiglitazone as a control in the pooled estimate.…”
supporting
confidence: 91%
“…However, a systematic analysis of the data concerning B12 status and metformin usage has not been carried out to date specifically in patients with Type 2 Diabetes. Two recent meta-analyses [8,9] have shown a reduction in B12 levels in populations with metformin use but both used a mixed population of patient types (e.g. diabetes, polycystic ovary syndrome, hyperlipidaemia).…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis, 15 an examination of absolute B 12 levels from 22 studies (pooled N = 4,302) identified lower B 12 levels, by 65.8 (95% CI, 53.6-78.1) pmol/L, in association with metformin treatment; heterogeneity was high (I 2 = 98%), but the risk of publication bias was considered low. The result narrowly missed statistical significance when only RCT data (10 trials; pooled N = 897) were examined; B 12 levels were lower in the metformin group by 30.9 (95% CI, −3.7 to 66.7) pmol/L.…”
Section: Metformin and The Risk Of Lactic Acidosismentioning
confidence: 82%
“…13,14 Metformin and Vitamin B 12 Metformin impairs the absorption of vitamin B 12 ; however, B 12 levels may be maintained in the normal range for months to years until the hepatic stores of the vitamin are depleted. Long-term treatment with metformin has been associated with clear evidence of low B 12 levels, and even of biochemical B 12 deficiency, as evident from the results of 2 meta-analyses, 15,16 presented below. Metformin: association with low B 12 levels.…”
Section: Metformin and The Risk Of Lactic Acidosismentioning
confidence: 96%
See 1 more Smart Citation